2016
DOI: 10.3892/ijo.2016.3354
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CXCR4 and CXCR7 with various stem cell markers in paired human primary and recurrent glioblastomas

Abstract: Abstract. The chemokine CXCL12 (also termed SDF-1, stromal cell-derived factor-1) and its receptors CXCR4 and CXCR7 are known to play a pivotal role in tumor progression including glioblastomas (GBM). Previous investigations focused on the expression and functional roles of CXCR4 and CXCR7 in different GBM cell subpopulations, but comparative analysis in matched primary versus recurrent GBM samples are still lacking. Thus, here we investigated the expression of CXCR4 and CXCR7 on mRNA and protein level using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It has been reported that CXCR4 is overexpressed in many tumor cells, including glioma, colorectal, breast, lung, prostate and cervical cancer (24). Consistently, high expression of CXCR4 was observed in highly invasive glioma stem cells (5). SDF-1α promotes tumor growth in a paracrine fashion by directly stimulating tumor cell proliferation and survival via CXCR4.…”
Section: Introductionmentioning
confidence: 56%
“…It has been reported that CXCR4 is overexpressed in many tumor cells, including glioma, colorectal, breast, lung, prostate and cervical cancer (24). Consistently, high expression of CXCR4 was observed in highly invasive glioma stem cells (5). SDF-1α promotes tumor growth in a paracrine fashion by directly stimulating tumor cell proliferation and survival via CXCR4.…”
Section: Introductionmentioning
confidence: 56%
“…These properties suggest that CXCR4 antagonists may help control this disease. CXCR4 expression varies significantly among different subtypes of GBM and in glioblastoma stem‐like cells (GSCs) 188–192 . Low expression of CXCR4 due to processes such as promoter hypermethylation might predict favorable overall survival.…”
Section: Cxcr4 In Cancer Development and Progression: Tumor Examplesmentioning
confidence: 99%
“…Nanog is expressed in various kinds of human tumors, including glioblastoma ( Figure 3 a), the most common malignant primary brain tumors [ 18 , 46 , 47 ]. On the other hand, CXCR4 controls the migration of neuronal cells [ 48 , 49 ], and it is the most common chemokine receptor expressed by many cancer cells, including glioblastoma [ 36 , 50 ], where CXCR4 plays a role in cancer cell migration [ 51 ]. To find out if h-NANOG can regulate CXCR4 expression in human cancer cells, we studied how changes in h-NANOG level affected the expression of CXCR4 in human glioblastoma and astrocytoma cell lines.…”
Section: Resultsmentioning
confidence: 99%